using formula simplify the two questions
Attachments:
![](https://hi-static.z-dn.net/files/db2/01fbca3621d6e22522c17c872527a858.jpg)
Answers
Answered by
1
Answer:
It is solved using (a-b)^3= a^3-3a^2b+3ab^2+b^3
997^3=(1000-3)^3=1000^3-3×1000^2×3+3×1000×3^2-3^3=1000000000-9000000+27000-27=991026973
89^3=(100-11)^3=100^3-3×100^2×11+3×100×11^2-11^3=1000000-330000+36300-1331=704969
Hope it helps.
If yes then mark it as brainliest!!!
yeetme609:
thank you
Similar questions
English,
3 months ago
Math,
3 months ago
English,
6 months ago
English,
6 months ago
Social Sciences,
1 year ago